IMPACT OF COVID-19 ON REAL ESTATE AND CONSTRUCTION SECTOR - Ojas Singh Garcha, Raghav Aggarwal, Megh Dave, Aditya Modi (EPRA International Journal of Economic and Business Review(JEBR), 2022)
COVID-19 outbreak is the greatest global health crisis in many years. It has had a dramatic effect on workforces and workplaces all around the world, as it has spawned a massive change in the working atmosphere and raised the level of employees’ concerns about their mental health and physical wellbeing. The construction industry has been significantly affected by the COVID-19 pandemic and has been challenged to improve the safety and wellbeing of its workforce. Overall this sector was impacted negatively but not that much due to government and this sector is again regaining control at a faster pace post covid as compared to other sectors.